1968
DOI: 10.1071/ar9680381
|View full text |Cite
|
Sign up to set email alerts
|

The nature of the perennial response in Mediterranean grasses. I. Water relations and summer survival in Phalaris

Abstract: An important factor in the survival of Phalaris tuberosa, a typical Mediterranean perennial grass, is the ability of its deep root system to supply water during the summer to the dormant culms at the soil surface. This behaviour contrasts with that of the related annual P. minor, which is unable to exploit subsoil moisture, and dies as soon as the surface moisture is exhausted. The volume of water supplied by the perennial roots is sufficient to offset transpiration losses and maintain a favourable water balan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(47 citation statements)
references
References 0 publications
3
44
0
Order By: Relevance
“…3a,b). Water supplied by perennial deep roots ( ‡ 1.5 m) is a core component of the survival strategy of some perennial grasses to survive summer drought (McWilliam & Kramer, 1968) and may also represent an important trait to sustain low rates of carbon assimilation in Lyginia (Fig. 3b).…”
Section: Discussionmentioning
confidence: 99%
“…3a,b). Water supplied by perennial deep roots ( ‡ 1.5 m) is a core component of the survival strategy of some perennial grasses to survive summer drought (McWilliam & Kramer, 1968) and may also represent an important trait to sustain low rates of carbon assimilation in Lyginia (Fig. 3b).…”
Section: Discussionmentioning
confidence: 99%
“…In phalaris, the early onset and high level of senescence of herbage were observed to reduce transpiration (McWilliam 1968) while the development of an extensive root system and/or superior hydraulic conductance to maximise soil water uptake was noted as being important for ongoing production under drying conditions in tall fescue (Garwood and Sinclair 1979). Dehydration-avoiding plants are able to survive extended dry spells but can only do so if able to maintain high tissue water status.…”
Section: Dehydration Avoidance/delay and Rooting System Improvementmentioning
confidence: 99%
“…Dehydration-avoiding plants are able to survive extended dry spells but can only do so if able to maintain high tissue water status. Indeed, McWilliam and Kramer (1968) demonstrated in phalaris that dehydration avoidance through the development of an extensive, deep root system (Cashmore 1934) and the ability to readily senesce foliage during summer is of great importance for the maintenance of the high plant water content that is typically observed in this grass. They showed that if this water harvesting ability is compromised by severing the root system, the plants rapidly die.…”
Section: Dehydration Avoidance/delay and Rooting System Improvementmentioning
confidence: 99%
“…The reduction in leaf tissue reduces total plant water loss (Gepstein, 2004;Munne Bosch and Alegre, 2004). A minimum water supply to the meristematic tissues is maintained (Karcher et al, 2008;McWilliam and Kramer, 1968;Volaire and Lelievre, 2001), and high concentrations of fructans and dehydrins contribute to osmoregulation and membrane stabilisation of these tissues (Hincha et al, 2000(Hincha et al, , 2002. High carbohydrate reserves are associated with superior plant resilience and recovery after severe drought (Boschma et al, 2003).…”
Section: Breeding For the Future Climatementioning
confidence: 99%